2016
DOI: 10.4103/0971-5916.198682
|View full text |Cite
|
Sign up to set email alerts
|

An audit of colistin use in neonatal sepsis from a tertiary care centre of a resource-limited country

Abstract: Background & objectives:Sepsis due to multidrug-resistant Gram-negative pathogens is a challenge for clinicians and microbiologists and has led to use of parenteral colistin. There is a paucity of data regarding safety and efficacy of intravenous colistin use in neonates. The objective of this retrospective analysis was to study the efficacy and safety of intravenous colistin in the treatment of neonatal sepsis.Methods:An audit of the data from neonates, admitted to a neonatal intensive care unit of a tertiary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 19 publications
4
15
0
Order By: Relevance
“…As expected, small for GA and low birthweight babies had higher mortality. These findings are consistent with several other studies globally 27 32. The absence of deteriorating clinical signs and laboratory parameters was significantly associated with survival, findings which are consistent and biologically plausible 33.…”
Section: Discussionsupporting
confidence: 92%
“…As expected, small for GA and low birthweight babies had higher mortality. These findings are consistent with several other studies globally 27 32. The absence of deteriorating clinical signs and laboratory parameters was significantly associated with survival, findings which are consistent and biologically plausible 33.…”
Section: Discussionsupporting
confidence: 92%
“…Both gram-positive and gram-negative organisms showed high susceptibility to Carbapenems, a similar finding to other studies conducted both inside and outside Nepal [11,12,17]. Similarly, gram-negative organisms showed high susceptibility to Colistin, which is consistent with the findings of Jessan Bonny et al [20].…”
Section: Discussionsupporting
confidence: 90%
“…The decreased microbial diversity in the patients with sepsis is consistent with reports from studies involving adult ICU patients in critical condition [34]. Sepsis caused by drug-resistant A. baumannii and other Gram-negative bacilli is a common challenge for clinicians and microbiologists [35]. Similar to the findings reported here, previous studies have found that certain species of Acinetobacter from the environment and hospitals were closely associated with lung infections [36,37].…”
Section: Discussionsupporting
confidence: 89%